2007
DOI: 10.1074/jbc.m703303200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Tat Transport of Unstructured, Small, Hydrophilic Proteins

Abstract: The twin-arginine translocation (Tat) system is a protein translocation system that is adapted to the translocation of folded proteins across biological membranes. An understanding of the folding requirements for Tat substrates is of fundamental importance for the elucidation of the transport mechanism. We now demonstrate for the first time Tat transport for fully unstructured proteins, using signal sequence fusions to naturally unfolded FG repeats from the yeast Nsp1p nuclear pore protein. The transport of un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
70
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 43 publications
4
70
0
Order By: Relevance
“…The FG repeats of this construct, named RR-(FG5)-GFP, thus serve as an unstructured linker peptide which connects the signal peptide to a folded GFP domain. The RR-(FG5) construct without GFP has recently been demonstrated to be Tatdependently translocated (20). We now found that an additional folded GFP domain at the C terminus completely blocked translocation (Fig.…”
Section: E Coli Tata Can Form Orderedsupporting
confidence: 60%
See 1 more Smart Citation
“…The FG repeats of this construct, named RR-(FG5)-GFP, thus serve as an unstructured linker peptide which connects the signal peptide to a folded GFP domain. The RR-(FG5) construct without GFP has recently been demonstrated to be Tatdependently translocated (20). We now found that an additional folded GFP domain at the C terminus completely blocked translocation (Fig.…”
Section: E Coli Tata Can Form Orderedsupporting
confidence: 60%
“…For analyses of subcellular targeting of Tat substrates, we used a high potential iron-sulfur protein (HiPIP) Tat signal peptide fusion to five unfolded FG repeats (FG5) from Nsp1p of yeast as expressed from the rhamnose-regulated vector pBW-R5 or its twin-lysine derivative pBW-R5-KK (20). To construct expression vectors for C-terminal green fluorescent protein (GFP) fusions of RR-(FG5) or KK-(FG5), gfp was amplified using pTB-DG (17) as template and the primers gfp-SacII-F (5Ј-AGG GCC CGC GGG TAA AGG AGA AGA ACT TTT CAC-3Ј) and gfp-XhoI-R (5Ј-GTC TGC TCG AGT TAT TTG TAT AGT TCA TCC ATG CC-3Ј), the fragment was cut with SacII and XhoI and cloned into the corresponding sites of pBW-R5 or pBW-R5-KK, resulting in pBW-R5-gfp and pBW-R5-gfp-KK, respectively.…”
Section: Strains and Growthmentioning
confidence: 99%
“…An advantage of FLI-TRAP is that, unlike the Y2H and B2H systems, it does not rely on DNA binding; thus, it is not susceptible to spurious transcriptional activation. Another advantage of this approach is that the tendency of the Tat system to export globular, soluble proteins that do not possess exposed hydrophobic segments (30,31,48,49) provides a built-in safeguard against false positives arising from the interaction of misfolded proteins (misfolded complexes will be blocked for Tat-dependent transport). Because the assay requires the interacting pair to remain associated during membrane transport, it stands to reason that relatively weak interactions (K D Ն1 M) will not be selected.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have proposed that an RR signal sequence might first interact with membrane lipids (25,26) before being handed over to the TatBC receptor complex. Although unfolded polypeptide chains can be translocated by the Tat apparatus (27)(28)(29), folding of a Tat substrate generally is a prerequisite for its transport (30 -34). Tat translocases were shown to discriminate against improperly folded substrates (30,35,36), but it is not understood how this is mechanistically achieved.…”
mentioning
confidence: 99%